Peso y mortalidad en la primera semana de vida de lechones tratados con un derivado comercial de calostro bovino (2000)
ABSTRACT: 506 piglets of a Colombian nucleus farm were studied to determine the effect of an oral treatment at birth with 3cc of bovine commercial colostrum, on their weight at seven days of age. The low birth weight piglets-LBWP, had significantly less weight, tan normal weight piglets at 7 days of age (p < 0.01). The treatment had a strong effect by increasing weight at seven days of age (p < 0.05). It was found that there is association between low birth weight condition and higher mortality at the first week of life (p < 0.01). The treatment with a bovine commercial colostrum was effective, specially on the LBWP at seven days of age (p < 0.05).